Kathy Smith : [videorecording (DVD)] : total body lift : sculpt a leaner younger looking you. - Smith, Kathy (Lions Gate Entertainment, 2008)
Viewers can sculpt a leaner, younger-looking body that defies gravity with exercises that increase strength and energy. The total workout includes: Warm-Up; Upper Body Lift; Leg Lift; Butt Lift; and Tummy Lift.